2020
DOI: 10.3390/v12060689
|View full text |Cite
|
Sign up to set email alerts
|

HHV-6 Infection and Chemokine RANTES Signaling Pathway Disturbance in Patients with Autoimmune Thyroiditis

Abstract: The aim of this study was to investigate the role of human herpesvirus-6 (HHV-6) in autoimmune thyroiditis (AIT) development. We examined the possible involvement of HHV-6 gene expression encoding immunomodulating proteins U12 and U51 in AIT development and their role in the modulation of chemokine signaling. One hundred patients with autoimmune thyroiditis following thyroidectomy were enrolled in this study. Nested polymerase chain reaction (nPCR) was used to detect the HHV-6 sequence in DNA samples. Reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Such spread combined with immunomodulating properties of HHV-6 ensures its lifelong persistence within the host. In previous studies we also showed dominance of HHV-6 activity in thyroid tissue and the absence of it in peripheral blood ( 7 , 16 ). Since U12 and U51 can be expressed on infected cell’s surface, these proteins could be more frequently exposed to the immune system, than for example, major capsid protein, as virus remains in solid tissues during the cell-to-cell spread.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Such spread combined with immunomodulating properties of HHV-6 ensures its lifelong persistence within the host. In previous studies we also showed dominance of HHV-6 activity in thyroid tissue and the absence of it in peripheral blood ( 7 , 16 ). Since U12 and U51 can be expressed on infected cell’s surface, these proteins could be more frequently exposed to the immune system, than for example, major capsid protein, as virus remains in solid tissues during the cell-to-cell spread.…”
Section: Discussionsupporting
confidence: 71%
“…Results from our own and other studies led us to believe that the chemokine receptors encoded by HHV-6 (U12 and U51) could be involved in the development of AIT. Firstly, we have observed that the chemokine receptors are expressed in the thyroid gland tissues of AIT patients and that the levels of chemokine RANTES, which can be bound and downregulated by the viral chemokine receptors ( 15 ), are significantly decreased in AIT patients plasma samples ( 16 ). Secondly, U12 and U51 can be expressed on infected cell surfaces and they possess structural and functional similarities with human chemokine receptors ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our latest manuscript, we show high frequency of HHV-6 U12 and/or U51 genes' mRNA presence in thyroid gland tissues acquired from AIT patients [16]. Proteins encoded by these genes are structurally similar to cellular G protein-coupled receptors like human CCR1, CCR3 and CCR5 [10,12].…”
Section: Discussionmentioning
confidence: 86%
“…U51 is a positive regulator of HHV-6A replication that might be related to cell-cell spread and may induce leukocyte migration in response to chemokine gradients (Zhen et al, 2005;Catusse et al, 2008). Recently, the presence of HHV-6, and vGPCRs U12 and U51 mRNA, was detected in thyroid gland tissues of patients with autoimmune thyroiditis (AIT) (Sultanova et al, 2020). Moreover, CCL5 levels in blood plasma were lowered in patients with AIT in which U12 and U51 gene expression was detected, indicating a potential role for these vGPCRs in influencing CCL5 signaling in AIT.…”
Section: Viral G Protein-coupled Receptors In a Viral Settingmentioning
confidence: 99%